Interactions between NSAIDs and Alcohol in the Context of Clinical Practice – A Review of Studies - Dominiczak, Kinga; Szafrańska, Katarzyna; Kopaczyńska, Adrianna; Janiak, Aleksandra; Niemirka, Szymon; Grądalski, Łukasz; Dębicki, Filip (Quality in Sport, 2025)
Introduction: Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used pharmacological agents with potent anti-inflammatory, analgesic, and antipyretic properties. Due to their broad application and availability, both prescription and over-the-counter, NSAIDs are highly popular across various age groups. Millions of people worldwide use these medications daily, making them one of the most commonly utilized drugs. On the other hand, ethanol, one of the most widely consumed psychoactive substances, is widely ingested globally. Both alcohol and NSAIDs undergo complex pharmacokinetic processes, including absorption, distribution, metabolism, and elimination. The co-existence of these substances in the body can lead to significant interactions that affect the efficacy of therapy and increase the risk of adverse effects. The objective of this study is to review the literature concerning interactions between NSAIDs and alcohol, with a particular emphasis on the impact of these interactions on usage practices and health outcomes. The study discusses the mechanisms of action of both substances, their effects on the gastrointestinal system, liver, and other organs, as well as the potential risks associated with their concurrent use. Aim of study: The aim of this study is to summarize the available knowledge about how alcohol influence on metabolism of non-steroidal anti-inflammatory drugs in human. Particular emphasis has been placed on its impact on the gastrointestinal, renal, and cardiovascular systems, which have been thoroughly analyzed and summarized. Material and methods: The literature available in PubMed, and the Google Scholar database was reviewed using the following keywords: , non-steroidal anti-inflammatory drugs”, , alcohol”, , COX-1”, , COX-2”